Andrew Beckett's Fight For Human Rights In Jonathan Demme's Philadelphia Movie ( 1993 ): An Individual Psychological Approach - Oktafiyantri, Dewi, Dr. Phil. Dewi Candraningrum, M.Ed, Nur Hidayat, M.Pd (2014)
The major problem of this study is to reveal Andrew Beckett's fight for human right in Jonathan Demme's Philadelphia movie. The objective of this study is to analyze the movie based on its structural elements, and based on individual psychological approach. In analyzing Philadelphia, the writer uses qualitative method and Individual Psychological Aapproach. The object of the study is Jonathan Demme's Philadelphia movie published in 1993 by Hollywood studio picture. The primary data source is the movie and its script, and the secondary data sources are the other data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive analysis. The outcome of the study shows that all of the elements of the movie compose one unity. Fight for human right of the major character in this movie, matched with the basic principles of Adler to overcome his life problem and makes positive and negative impacts for his own self and other people around him.